PENGARUH PENEGAKAN HUKUM DAN GENDER TERHADAP PENGGELAPAN PAJAK DIMEDIASI OLEH MORAL PAJAK - Zirman Zirman (Akuntabilitas, 2015)
This study aimed to examine the effect of law enforcement and gender on taxevasion, mediated by moral taxes. The population in this study is an individual taxpayer whois registered on tax office of Prtama Tampan. The sampling technique used is conveniencesampling with total sample of 64 individual tax payer. The technique analysis used isStructural Equation Model with software Smart PLS. The results showed that law enforcementsignificant positive effect on tax morale, while gender does not affect on tax morale. Taxmorale significant negative effect on tax evasion. The analysis also showed tax moralemediates the effect of law enforcement on tax evasion, against tax morale does not mediatethe effect of gender on tax evasionDOI: 10.15408/akt.v8i2.2768